Herausforderungen und Perspektiven zur Ermöglichung dualer Karrieren durch den Einsatz digitaler Medien - Linda Heise (FernUniversität Hagen, 2018)
An important challenge of higher educational institutions is the inclusion of non-traditional learners. The following paper presents a project, which researched the challenges and special needs of student top athletes. First the paper will present the results of a qualitative study about the challenges and conditions of their study programs and commitments of student top athletes at the University of Applied Science Mittweida. Based on this results a blended learning scenario in combination with the flipped classroom has been introduced and tested.